Detection of a synthetic sex steroid in the American crocodile (Crocodylus acutus): Evidence for a novel environmental androgen. (August 2017) - Murray, Christopher M.; Merchant, Mark; Easter, Michael; Padilla, Sergio; Garrigós, Davinia B.; Sasa Marin, Mahmood; Guyer, Craig
Abstract: Endocrine-disrupting contaminants (EDC's) are well known to alter sexual differentiation among vertebrates via estrogenic effects during development, particularly in organisms characterized by temperature-dependent sex determination. However, substances producing androgenic effects typically lack potency when tested in laboratory settings and are virtually unstudied in field settings. Here, we assay levels of a synthetic androgen, 17α-methyltestosterone (MT), in a heavily male-biased population of American crocodiles in the Tempisque River Basin of Costa Rica based on the recent hypothesis that this chemical is an EDC in developing crocodilian embryos. The presence of MT was documented in all field-collected samples of egg yolk and in plasma of all age classes in among population of crocodiles. Hatchlings exhibited higher plasma MT concentrations (102.1 ± 82.8 ng/mL) than juveniles (33.8 ± 51.5) and adults (25.9 ± 20.8 ng/mL). Among populations, crocodiles captured in the Tempisque River (62.9 ± 73.7 ng/mL) were higher in MT concentration than those from Tarcoles (13.3 ± 11.4 ng/mL) and negative controls (0.001 ± 0.0002 ng/mL). A mechanism for the bio-transport of MT and its subsequent effects is proposed. Highlights: A novel suite of ecotoxin, environmental androgens, is empirically introduced. The presence of methyltestosterone is documented in wild crocodile populations. Chronic exposure and trans-generational transport of methyltestosterone is revealed.